Toward Normalization of Defamation Law: The U.K. Defamation Act of 2013 and the U.S. SPEECH Act of 2010 as Responses to the Issue of Libel Tourism. Issue 1 (2nd January 2017) - Watson, Roxanne; Roldan, Roberto; Faza, Andres
Abstract : In the wake of several high-profile libel actions brought by U.S. celebrities and foreign businessmen in London because of more favorable defamation laws there, London was dubbed the "libel tourism capital of the world." The U.S. response in 2010 was the passage of the SPEECH Act, preventing courts from enforcing libel judgments from foreign jurisdictions not providing the same level of protection as the United States. Similarly, in 2013 the United Kingdom responded to international and national criticism by passing the Defamation Act to address the loophole in its system that caused the abuse. Both acts have been criticized, the first for its aggressiveness, and the second for its conservative nature. This article examines the development of the law of defamation in the two jurisdictions and analyzes the content of both statutes, along with their criticisms, proposing international cooperation to address the issue of libel tourism.